The cure of ageing: vitamin D—magic or myth?. Issue 1020 (21st October 2010) - Chu, Michael P; Alagiakrishnan, Kannayiram; Sadowski, Cheryl
Abstract : Vitamin D was initially thought only to function in calcium homeostasis. However, it has multiple roles in human health, including neuromuscular and immune modulation. Recently, its deficiency is increasingly implicated in many diseases. This discovery has led both popular culture and research to find ways that vitamin D can either treat or prevent many diseases. Since vitamin D not only affects the expression of many genes, but also has intra-individual pharmacokinetic variation, a simplistic cause and effect between vitamin D deficiency and illnesses should not be expected. Older adults pose a challenge not only because diseases become more prevalent with ageing, but they also are often complicated with other comorbidities. This article reviews the link of vitamin D deficiency and the associated medical conditions in middle aged and older adults. It also examines the variability in testing vitamin D values and evaluates dosing recommendations based on current evidence.